Faunistic and bio-ecological accounts on the aphid fauna of Lombardy region (Northern Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper deals on the aphid fauna of Lombardy region, northern side of the Italian peninsula, which is inclusive so far of 431 species and subspecies. The check-list includes either aphid species deriving from the identification of collected samples, as well as those species previously recorded for that territory. For the latter aphids bibliographic refereces are reported, while for the newly surveyed samples data on host plant species and collecting localities are given. A total number of 131 new regional aphid records are obtained from all collected samples. The latter are also inclusive of fifteen aphid species not yet known for Italy, on which short taxonomic and biological notes are given.
Keywords: aphid fauna; Lombardy region; Italy